Design techniques for cogging torque reduction in a fractional-slot PMBLDC motor - Petkovska Lidija, Lefley Paul and Cvetkovski Goga (Emerald Publishing Limited, 2020)
This paper presents the design techniques applied to a novel fractional-slot 6/4 pole permanent magnet brushless direct current (PMBLDC) motor, for cogging torque reduction. The notable feature of this motor is the simplicity of the design and low production cost. The purpose of this paper is to reduce the peak cogging torque of the motor. The focus is put on the stator topology tuning, and a new design for the stator poles is proposed. By determining the optimum stator pole arc length and the best pole shoe thickness, the cogging torque is significantly reduced. This new optimised motor design has been analysed in detail. The validation of the results is documented with respective figures and charts.
Keywords: Permanent magnet machine, Finite element analysis, Shape optimisation, Torque calculation, Torque ripple, Cogging torque, Electromagnetic torque, PM brushless DC motor